Social implications and challenges of e-business - Li 1965- (Information Science Reference, 2007)
"This book explores the social implications and challenges of E-Business and E-Commerce regarding social inclusion and exclusion, the social shaping of e-business technologies, the changing nature and patterns of work and social activities, and online identity, security, risks, trust and privacy. It also explores the applications of E-Business technologies and principles in non-business activities and the challenges involved"--Provided by publisher.